2014
DOI: 10.3201/eid2009.131882
|View full text |Cite
|
Sign up to set email alerts
|

Household-Level Spatiotemporal Patterns of Incidence of Cholera, Haiti, 2011

Abstract: A cholera outbreak began in Haiti during October, 2010. Spatiotemporal patterns of household-level cholera in Ouest Department showed that the initial clusters tended to follow major roadways; subsequent clusters occurred further inland. Our data highlight transmission pathway complexities and the need for case and household-level analysis to understand disease spread and optimize interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Additionally, despite the high spatial-resolution of our data, long-cycle transmission within a single neighborhood is possible and would instead be captured by the within-neighborhood transmission coefficient ( β i ). It is probable that the epidemic resulted from multiple disparate transmission routes, a hypothesis consistent with recent models of the Haitian outbreak [ 34 , 39 ]. Our analysis could not investigate any specific alternative pathway, although contemporary reports of human waste used as fertilizer for food crops highlights one possible alternative route, which has been observed in other outbreaks as well [ 40 ].…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, despite the high spatial-resolution of our data, long-cycle transmission within a single neighborhood is possible and would instead be captured by the within-neighborhood transmission coefficient ( β i ). It is probable that the epidemic resulted from multiple disparate transmission routes, a hypothesis consistent with recent models of the Haitian outbreak [ 34 , 39 ]. Our analysis could not investigate any specific alternative pathway, although contemporary reports of human waste used as fertilizer for food crops highlights one possible alternative route, which has been observed in other outbreaks as well [ 40 ].…”
Section: Discussionsupporting
confidence: 64%
“…Changes in temperature [45] and precipitation [13, 15, 45] levels have been previously associated with the probability of subsequent cholera outbreaks. Local geographic features, such as highways [2], inland waterbodies (lakes/rivers) [2, 46], and coastline/shoreline [5, 47] have also been associated with elevated disease frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Transmission models that only include ingestion of V. cholerae through environmental point sources, or environment-to-human transmission, cannot explain the steep rise in case numbers usually seen in outbreaks [27,45,47]. Spatiotemporal analyses of cholera in endemic and epidemic settings have instead demonstrated clusters of cases within 200m distances of case-households during the first five days after index cases present with symptoms [48][49][50], and a 100-fold higher risk of household contacts of cases to contract the disease compared to those outside the household [43,[51][52][53][54]. Research on the genomics of cholera transmission has also demonstrated strong phylogenetic similarities among same-household cases [43,[55][56][57][58], and a recent paper found 80% of transmission occurs between people who share a household [55].…”
Section: Introductionmentioning
confidence: 99%